2020
DOI: 10.1177/0022034520925421
|View full text |Cite
|
Sign up to set email alerts
|

Oral Mucositis: An Update on Innate Immunity and New Interventional Targets

Abstract: Oral mucositis (OM), a common debilitating toxicity associated with chemo- and radiation therapies, is a significant unmet clinical need for head and neck cancer patients. The biological complexities of chemoradiotherapy-induced OM involve interactions among disrupted tissue structures, inflammatory infiltrations, and oral microbiome, whereby several master inflammatory pathways constitute the complicated regulatory networks. Oral mucosal damages triggered by chemoradiotherapy-induced cell apoptosis were furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 82 publications
(126 reference statements)
1
29
0
Order By: Relevance
“…OM is one of the most incapacitating side effects of RT, CT, or CRT for HNC and thus one of the most extensively studied ( 5 , 49 51 ). The World Health Organization’s OM Toxicity Scale ranges from grade 1 to 4: (1) soreness with or without erythema, (2) ulcers with erythema without dysphagia to solid foods, (3) ulcers with extensive erythema and dysphagia to solid foods, and (4) mucositis with complete dysphagia ( 5 ).…”
Section: Radiation Therapy and Changes In The Head And Neck Microbiomementioning
confidence: 99%
“…OM is one of the most incapacitating side effects of RT, CT, or CRT for HNC and thus one of the most extensively studied ( 5 , 49 51 ). The World Health Organization’s OM Toxicity Scale ranges from grade 1 to 4: (1) soreness with or without erythema, (2) ulcers with erythema without dysphagia to solid foods, (3) ulcers with extensive erythema and dysphagia to solid foods, and (4) mucositis with complete dysphagia ( 5 ).…”
Section: Radiation Therapy and Changes In The Head And Neck Microbiomementioning
confidence: 99%
“…The findings of our study showed that oral changes caused by oral mucositis were present at 1st CT week. This fact could be explaining because the complex pathophysiological processes of chemoradiotherapy induced OM starts immediately after the administration of the cytotoxic agents ( 10 , 11 ). The early recognition of clinical signs of oral mucositis and, especially, the anatomical sites commonly affected by chemoradiotherapy-induced OM is essential to prevent worsening of the condition.…”
Section: Discussionmentioning
confidence: 99%
“…The early recognition of clinical signs of oral mucositis and, especially, the anatomical sites commonly affected by chemoradiotherapy-induced OM is essential to prevent worsening of the condition. This approach contributes, for example, to do not be necessary reduction and even cessation of cancer treatment ( 11 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in a follow-up Chernobyl study, 4 of 15 survivors reported experiencing xerostomia ( Gottlöber et al, 2001 ). Salivary damage and subsequent dry mouth can lead to a variety of problems, from difficulty chewing and talking to increased dental caries, oral mucositis, osteonecrosis, and so on ( Dirix et al, 2006 ; Gomez et al, 2011 ; Tolentino et al, 2011 ; Sroussi et al, 2017 ; Chen et al, 2020 ). While studies of the oral microbiome following a nuclear accident are limited, there are many research studies that examine the changes in the oral microbiota following head and neck radiation exposure in oncology ( Anjali et al, 2020 ).…”
Section: The Effects Of Radiation On the Microbiomementioning
confidence: 99%